Avaliação na captura de peixes com malhadeiras nos períodos do ciclo hidrológico e do dia em Lagos de Várzea, Amazonas, Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
Daily rhythm is the period of a day on which is based the entire life cycle having relevance in fish activity, since their movement promotes changes in the composition of the assemblies in response to changes in the environment. In this context the paper proposes to analyze the seasonal and daily variation of fish assemblages in floodplain lakes, AM, Brazil. The fish collection was held in the lake system floodplain Lago Grande de Manacapuru, Risk Island and Marchantaria Island during periods of flood and ebb full, located in the middle Solimões-Amazonas. The fish were caught with battery nets of various mesh sizes that remained in the water for 24 hours, with fish removal every six hours. After catching the fish were identified and grouped into periods of the day as the collection time (morning, 12 h; dawn, 6 h, overnight, 24-hour dark, 18 h) for each period. They were captured a total of 12 847 samples, distributed in 168 species belonging to 9 orders, 27 families. The most diverse group was followed by the Characiformes, Siluriformes, Clupeiformes and Perciformes. Triportheus angulatus was dominant in the flood and as full of Potamorhina latior was on the ebb, followed by Potamorhina latior, T. albus and P. nattereri in the flood, flood and ebb respectively. The taxonomic composition and structure of the meetings ranged from the times of the day in each period. In T. angulatus flood it was dominant at dawn and at night, while P. latior was dominant during the day and evening. In flood, T. angulatus remained the dominant at night and dusk, P. latior at dawn and Hemiodus "red tail" during the day. In the ebb P. nattereri was dominant in the early morning, H. edentatus during the day and P. latior in the evening and night periods. The correspondence analysis (CA) examined patterns of everyday occurrences for species with over 1% catches the periods of the hydrological cycle and identified strong association of the captured fish fauna in the morning and evening periods in dimension 1 and daytime and evening periods in dimension 2. in flood the CA identified strong association of catches in the daytime periods, night and dawn in one dimension and strong association at dawn in dimension 2. In the ebb CA showed a strong association during the day in one dimension on the other hand a strong association in dark times, night and dawn in dimension 2. In the statistical analysis to the ecological wealth descriptors (r), dominance (d), Shannon diversity index (H'), evenness (E) and CPUE (n) between the hours of the day the three hydrological periods the same indicated significant differences in CPUE (n) and wealth (S) hydrological period and day with higher CPUE(n) values on the ebb and wealth (S) in the flood. Regarding the 14 most abundant species significant differences were observed in T. angulatus capture and Pellona flavipinnis between the periods of the day and P. nattereri and Acestrorhynchus falcirostris between hydrological periods. The change in the composition and structure of fish assemblages throughout the day, observed in this study, is linked to the daily movement of the diurnal and nocturnal species, possibly related to food and predation. It is another factor that can influence the composition and structure of fish assemblages throughout the day is the visibility of gillnets by the species with the highest visual acuity during the day.
Keywords: Variação nictemeral; Diversidade de peixes; Ictiofauna; CIÊNCIAS AGRÁRIAS: RECURSOS PESQUEIROS E ENGENHARIA DE PESCA